To solve this system of equations, we can use the method of elimination.
First, let's multiply the first equation by 2 to make the coefficients of x the same but opposite signs:
-4x + 4y = -28
Now, we can add the two equations together to eliminate the x variable:
(2x + 6y) + (-4x + 4y) = 20 - 28
2y = -8
y = -4
Now, we can substitute the value of y back into one of the original equations to solve for x:
-2x + 2(-4) = -14
-2x - 8 = -14
-2x = -6
x = 3
Therefore, the solution to the system of equations is x = 3 and y = -4.
-2x+2y=-14
2x+6y=20
1 answer